View of Santa Clara Valley from the Eastern Hills - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic landscape of Santa Clara Valley from the Eastern foothills. The exact location is unknown. In the center of the image several large estates with orchards can be seen. In the center right of the image, three large water tanks stand on a hill. A golf course, probably the San Jose Country Club, with sand traps surrounds the water tanks and continues further downhill. On the far left and right of the image orchards can be seen planted on the hillside.